PENGARUH JARAK TANAM DAN TAKARAN PUPUK KOTORAN AYAM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG TANAH (Arachis hypogaea L.) Effect of Plant Spacing and Dose Chicken Manure Fertilizer On - Yayang1, Yayang; Amir, Nurbaiti; Hawalid, Heniyati (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2014)
This study aims to identify and study the effect of plant spacing and chicken manure fertilizers on growth and yield of peanut. This research was conducted at the Experimental Farm of the Faculty of Agriculture Land Dictionary C Universitas Muhammadiyah Palembang, Hamlet I Semambu Island Village, District of North Indralaya, Ogan Ilir South Sumatra, took place from May to August 2014. The method used is a plot design Separated (Split Plot Design) with nine combinations of treatments and three replications. The main plot (main plot) is a spacing (A), J1 20 cm x 20 cm, 30 cm x 20 J2 cm, J3 40 cm x 20 cm, as a subplot (sub-plots) is the dose of compost (P), P1 5 tons / ha, P2 10 tons / ha, P3 15 tons / ha. Parameters observed that plant height (cm), number of primary branches (branch), the overall weight of pod (g), number of pods containing (pod), the number of empty pods (legumes), berangkasan wet weight (g), dry berangkasan weight (g ), 100 seed weight (g). Based on the results of analysis of variance showed that the spacing of chicken manure fertilizer rate and not significant for all variables observed. Treatment interaction effect was not significant